Silent killer – a case of sudden death linked to lymphocytic thyroiditis - Mussadik, Umul Khairil Fatimah; Zaki, Hafizatul Solehah; Hasim, Husna Syaza; Chng, Kay Ly (Malaysian Society of Pathologists, 2025)
Introduction: Sudden unexpected death (SUD) in a healthy young adult presents a challenging scenario that forensic pathologists often encounter. Although they are rare, thyroid diseases such as hyperthyroidism, hypothyroidism, and lymphocytic thyroiditis can contribute to SUD. Comprehensive investigations, including thyroid histological evaluation, are critical to identify underlying causes. This report discusses a rare case of lymphocytic thyroiditis in a young male who died unexpectedly, highlighting the forensic value of thyroid pathology in SUD cases. Case Report: A 25-year-old Bangladeshi male, with no known comorbidities, was found unresponsive in bed and was brought to the hospital, where resuscitation efforts in the emergency department were unsuccessful. He had no complaints of health issues in the past two weeks before his death. There was no family history of SUD. Externally, there was no evidence of injury or systemic disease. Gross examination of vital organs, including the heart and brain, was unremarkable. A cricothyroidotomy incision partially obscured the thyroid gland. However, histological analysis revealed lymphocytic infiltration, follicular destruction in the thyroid glands, and fibrosis in the sinoatrial (SA) node. Extensive toxicological tests were negative and no thyroid function tests or molecular autopsy were performed. Conclusion: Lymphocytic thyroiditis should be considered in SUD cases, even with unremarkable gross findings or nonspecific clinical history. Routine microscopic thyroid examination could reveal subtle yet significant conditions contributing to SUD. Establishing standardised autopsy guidelines focusing on thorough thyroid assessment may improve post-mortem diagnostics and enhance the understanding of thyroid pathology in SUD.